The Roles of Host Noncoding RNAs in Mycobacterium tuberculosis Infection - Wei, Li; Liu, Kai; Jia, Qingzhi; Zhang, Hui; Bie, Qingli; Zhang, Bin (Frontiers in Immunology, 2021)
Tuberculosis remains a major health problem. Mycobacterium tuberculosis, the causative agent of tuberculosis, can replicate and persist in host cells. Noncoding RNAs (ncRNAs) widely participate in various biological processes, including Mycobacterium tuberculosis infection, and play critical roles in gene regulation. In this review, we summarize the latest reports on ncRNAs (microRNAs, piRNAs, circRNAs and lncRNAs) that regulate the host response against Mycobacterium tuberculosis infection. In the context of host-Mycobacterium tuberculosis interactions, a broad and in-depth understanding of host ncRNA regulatory mechanisms may lead to potential clinical prospects for tuberculosis diagnosis and the development of new antituberculosis therapies.